Antimicrobial resistance and outcomes of community-onset bacterial bloodstream infections in patients with type 2 diabetes. (December 2018) - Huang, Chung-Huei; Chiu, Cheng-Hsun; Chen, I-Wen; Hung, Shih-Yuan; Lin, Cheng-Wei; Hsu, Brend Ray-Sea; Huang, Yu-Yao
Highlights: Staphylococcus spp., E. coli and Klebsiella spp. were the leading pathogens in community-onset bloodstream infections. Antimicrobial-resistant bacterial infections resulted in a higher 30-day mortality rate. Lower serum albumin level may serve as a predictor for mortality. Abstract: Objectives: Antimicrobial resistance of bacterial pathogens in the diabetic population with infection is seldom investigated. This study evaluated the antimicrobial resistance and outcomes of community-onset bloodstream infections (CO-BSIs) in patients with diabetes. Methods: From 2007–2014, 1271 monomicrobial CO-BSIs and 178 polymicrobial CO-BSIs were identified in patients with type 2 diabetes from three teaching hospitals in Taiwan. Antimicrobial-resistant strains of the ten most prevalent bacterial pathogens in monomicrobial CO-BSIs were recorded and were defined according to individual drug resistance. The 30-day mortality rate and factors associated with outcome were analysed. Results: Antimicrobial-resistant strains were found in 33.7% (379/1125) of monomicrobial CO-BSIs involving the 10 most prevalent pathogens. The leading pathogens in these monomicrobial CO-BSIs were Staphylococcus spp. (33.8%; 430/1271), Escherichia coli (20.9%; 266/1271) and Klebsiella spp. (9.6%; 122/1271); antimicrobial-resistant strains accounted for 61.9%, 18.4% and 10.7% of each, respectively. A higher overall 30-day mortality rate was observed for patients infected by antimicrobial-resistant strains compared with antimicrobial-susceptible strains (9.5% vs. 5.5%; P = 0.011, log-rank test). A lower serum albumin level was a predictor of mortality after adjusting for antimicrobial-resistant strains and C-reactive protein level. Conclusions: Antimicrobial-resistant bacterial pathogens pose a serious threat to diabetic patients with CO-BSIs owing to a higher risk of mortality.